The relationship between product and international diversification: The role of experience - Mayer, Michael C. J.; Stadler, Christian; Hautz, Julia (Strategic Management Journal, 2015)
We establish prior diversification experience as a key determinant of the relationship between growth of product and international diversification. Prior diversification experience allows firms to overcome short‐run constraints on simultaneous diversification growth imposed by the difficulty to transfer tacit knowledge, ambiguous competencies, and limited absorptive capacity. Studying U.S. and European firms, we find a positive relationship between growth in product and international scope for firms with high and a negative one for those with little prior diversification experience. Further, we find that product diversification experience has greater impact than international diversification experience . Copyright © 2014 John Wiley & Sons, Ltd.